Sex differences in personality dysfunction in help-seeking adolescents - Cavelti, Marialuisa; Schenk, Jana; Sele, Silvano; Reichl, Corinna; Koenig, Julian; Mürner-Lavanchy, Ines M.; Kaess, Michael (Borderline Personality Disorder and Emotion Dysregulation, 2025)
INTRODUCTION: Understanding sex differences is crucial for improving diagnosis and treatment for personality disorders (PDs). This study aimed to investigate sex differences in personality dysfunction as per Criterion A of the DSM-5 Alternative Model of Personality Disorders in help-seeking adolescents. - METHODS: The sample comprised 706 adolescent patients (mean age = 15.4 years; 80.88% females). Personality dysfunction was assessed using the Semi-Structured Interview for Personality Functioning DSM-5 (STiP 5.1). - RESULTS: Females showed significantly higher overall personality dysfunction (Cohen's d = 0.36) compared to males, particularly in the self-functioning domain (d = 0.50), including identity (d = 0.52) and self-direction (d = 0.38). Sex differences in interpersonal functioning, particularly empathy, were statistically not significant, but females demonstrated greater impairments in intimacy compared to males (d = 0.23). Age did not moderate sex differences in personality dysfunction. Higher levels of personality dysfunction were associated with an increased likelihood of an alcohol use disorder and more severe psychosocial impairments in females compared to males. - DISCUSSION: The findings indicate that female adolescent patients exhibit greater impairments in personality functioning than males, with the difference being more pronounced in self-functioning than in interpersonal functioning. Results highlight the need for further investigation of the biological, psychological, and social factors driving these differences and call for the development of sex-sensitive diagnostic and interventional approaches to PDs.